Rap battles and rhetoric: Phonological figures of rhetoric in rap - Vázquez-Sánchez, Rubén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Rap battles in the freestyle are competitions that encourage the linguistic creativity of the participants, and poetic elements and resources are widely used to improve their scores in the competition. This research shows what the phonological rhetorical figures are, how these resources are used in the elaboration of the messages made by the freestylers and how the use of phonological licenses and recurrences and metric licenses are integrated in order to create a persuasive and ornate discourse, complementing the musical basis on which they have to create the speech.